Звіт про власний капітал : порядок складання та шляхи удосконалення - Линник, Олена Іванівна; Каверзін, О. О. (НТУ "ХПІ", 2010)
This article describes the methods for reporting on the equity of the elements taken into consideration the equity business. An opportunity for improving the structure of the Report of its maximum adjustment to the needs of management and control.
Keywords: облік; звітність; вклади; пасив балансу